Threshold dynamics of a bat-borne rabies model with periodic incubation periods. (October 2021) - Wang, Feng-Bin; Wu, Ruiwen; Yu, Xiao
Abstract: Bat-borne rabies is a viral infection caused by lyssaviruses . To explore the complex interaction between bats and cattle, we develop a periodic compartment system with seasonality, temperature-dependent incubation period and different control measures. We derive the basic reproduction number R 0 and show it determines the global dynamics. In particular, we prove the non-existence of positive periodic solutions in the critical case where R 0 = 1 . Numerically, we observe that sufficient long time-varying incubation periods could potentially increase the disease outbreak risk.